2018
DOI: 10.18203/2394-6040.ijcmph20180777
|View full text |Cite
|
Sign up to set email alerts
|

A study on complementary feeding practices among mothers in urban and rural areas

Abstract: Background: Adequate nutrition during infancy and early childhood is essential to ensure the growth, health, and development of children to their full potential. Complementary feeding is a process starting when breast milk alone is no longer sufficient to meet the nutritional requirements of infants, and therefore other foods and liquids are needed, along with breast milk. The objective was to study complementary feeding practices and the various factors influencing them in urban and rural areas.Methods: A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The related study mentioned that important to raise awareness and knowledge in improving complementary feeding practices through media to reduce undernutrition 26 . Education campaigns concerning feeding practices should not only to mothers but also for family members who are decision-makers like a mother-inlaw or older adult in the family 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The related study mentioned that important to raise awareness and knowledge in improving complementary feeding practices through media to reduce undernutrition 26 . Education campaigns concerning feeding practices should not only to mothers but also for family members who are decision-makers like a mother-inlaw or older adult in the family 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Adults have little less requirements of nutrients than infants and children for their building growth. The proper amount of nutrients in infants & children promote and support their rapid rate of growth while adults need nutrients to maintain the function and constant body weight [4]. Weaning feeding stars from 6 months of age.It should be nutritionally adequate and safe ,nutrients need the feed should be appropriate, however there are same problem faced by the mother or family, when the child is on compile feeding it often leads to problem body composition, climate and environment.Prerna Singhal, Seema jain, S K Garg, Harivansh Chopra in a study done on 2015 in Bangladesh found that complementary feeding was introduced before 6 months in one third babies and the amount was inadequate in same number of children [4].…”
Section: Discussionmentioning
confidence: 99%
“…The proper amount of nutrients in infants & children promote and support their rapid rate of growth while adults need nutrients to maintain the function and constant body weight [4]. Weaning feeding stars from 6 months of age.It should be nutritionally adequate and safe ,nutrients need the feed should be appropriate, however there are same problem faced by the mother or family, when the child is on compile feeding it often leads to problem body composition, climate and environment.Prerna Singhal, Seema jain, S K Garg, Harivansh Chopra in a study done on 2015 in Bangladesh found that complementary feeding was introduced before 6 months in one third babies and the amount was inadequate in same number of children [4]. The no of meals per day varied from child to child .It is also dependent on the socio-economic status of the family .The study recorded 36.66% participants giving 3 meals a day followed by 33.33% giving 2 meals a day .Only 30% of participants gives 4 meals a day .This has been observed that no of meals were dependent on the affordability and availability [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary foods must be nutritionally adequate, safe, and appropriately fed to meet the young child's energy and nutrient needs. 1 WHO recommends that, infants should receieve complementary foods at six months of age in addition to breast milk. It should be given initially 2-3 times a day between 6-8 months, increasing to 3-4 times daily between 9-11 months and 12-24 months, with additional nutritious snacks offered 1-2 times per day, as required.…”
Section: Introductionmentioning
confidence: 99%